Testing a new taxonomic model for the assessment of medical devices: Is it plausible and applicable? Insights from HTA reports and interviews with HTA institutions in Europe. Issue 2 (February 2019) - Fuchs, Sabine; Olberg, Britta; Perleth, Matthias; Busse, Reinhard; Panteli, Dimitra
Highlights: A new taxonomic model for medical devices (MDs) from a HTA viewpoint was tested. The distribution of 1237 European HTA reports on the taxonomic matrix confirmed its plausibility. Interviews with 16 representatives of European HTA institutions support the model's applicability. The model can be used to facilitate the selection of technologies for assessment. As a "learning model" the taxonomy can be adapted to reflect new developments and insights. Abstract: Objective: Medical devices (MDs) encompass a broad and heterogeneous range of technologies. While practices vary considerably across countries, MDs often find application in patient care with little or no evaluation of their effectiveness and safety following market approval. A recently proposed taxonomy of MDs considered devices from the viewpoint of Health Technology Assessment (HTA). The aim of the work presented here was to test its plausibility and applicability by considering real-world HTA practices. Methods: HTA reports on MDs from European institutions were collected in a systematic manner and the evaluated devices and/or related procedures were matched to a position on the taxonomy. Following this, representatives from 16 European HTA institutions were asked about the usefulness of the taxonomy in semi-structured interviews. Results: 1237 HTA reports (2004–2015) from 33 European institutions were included in the sample. The majority of reports was on technologies from the taxonomic positions initially estimated as having high relevance. Most of the experts interviewed stated that they found the taxonomy useful, particularly regarding its potential to aid in selecting technologies for assessment and to highlight potential methodological particularities per taxonomic position. Conclusions: Overall, the distribution of identified reports on the matrix confirmed that the initial estimation of the relevance and necessity of HTA provided in the taxonomic model is plausible. In addition, interviews with representatives of European HTA institutions showed that the taxonomy could be useful.